2017
DOI: 10.21776/ub.jiip.2017.027.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Potensi jerami sebagai pakan ternak ruminansia

Abstract: :The basic reason for poor performance of livestock in developing countries includes Indonesia, is qualitative fluctuations in the feed. Therefore knowledge in utilizing agroindustry byproduct as feedstuff to meet the nutrient requirement of animals is important. Rice straw is a crop residue of rice production and can be used as a feed for ruminants because it is easily and cheaply available in many Asian countries. Rice straws have low nutritive value and it is generally limited by several factors such as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
0
8
0
18
Order By: Relevance
“…This study revealed that the type of feed given to the cattle during the transportation consisted only rice straw with relatively low digestibility (30%), reported by Sudarwati and Susilawati 2013) and low crude protein (3%-5%, Yanuartono et al 2017). Improper feed storage in the ship affected the feed quality which influencing the total nutrient consumption.…”
Section: Resultsmentioning
confidence: 69%
“…This study revealed that the type of feed given to the cattle during the transportation consisted only rice straw with relatively low digestibility (30%), reported by Sudarwati and Susilawati 2013) and low crude protein (3%-5%, Yanuartono et al 2017). Improper feed storage in the ship affected the feed quality which influencing the total nutrient consumption.…”
Section: Resultsmentioning
confidence: 69%
“…Jerami padi memiliki kelemahan antara lain kandungan lignoselulosa yang tinggi, kandungan protein kasar (PK) yang rendah (Wachirapakorn et al, 2016), sifat amba yang tinggi dan kurang palatabel (Yanuartono et al, 2017). Guna mengatasi kekurangan nutrien jerami padi, biasanya peternak menambahkan hijauan lain yang memiliki kualitas yang lebih baik seperti kaliandra (Calliandra callothyrsus).…”
Section: Pendahuluanunclassified
“…Pelatihan pembuatan jerami padi fermentasi memberikan manfaat kepada peternak karena dapat meningkatkan kualitas jerami padi sebagai pakan ternak sehingga dapat membantu mengurangi pembelian pakan hijauan serta dapat memperbaiki produktivitas ternak di Desa Kenteng. Menurut Yanuartono et al (2017), bahwa kelemahan dari jerami padi sebagai pakan ternak adalah daya cerna dan nilai gizi yang rendah. Oleh karena itu, perlu pengolahan jerami padi, hal ini dimaksudkan untuk menurunkan kadar serat kasar yang tinggi dan meningkatkan kadar protein jerami padi, dengan proses amoniasi dan fermentasi menggunakan bantuan bakteri selulolitik (Wina, 2005).…”
Section: Kegiatan Penyuluhanunclassified